Analytical investigation on resolution calculation method for nonlinear temperature load of steel-concrete composite girders - Zhang, Chun-Ming; Wu, Wei-Hong; Xian, Wei (Frontiers in Materials, 2025)
This study establishes a thermo-mechanical coupling framework to elucidate the contribution mechanisms of nonlinear thermal loads in composite girders through thermal effect decomposition. A novel decomposition methodology for nonlinear temperature fields is developed based on the thermal effect equivalence principle, integrating cross-sectional deformation compatibility conditions to characterize the dynamic coupling between thermal responses and temperature loads. The proposed approach enables systematic decomposition of actual nonlinear temperature fields into three equivalent components: uniform, linear, and nonlinear temperature gradients. A computational framework incorporating statically indeterminate structural effects is subsequently formulated for comprehensive thermal response analysis. Four thermal loading models are comparatively investigated: field-measured temperature gradients, two theoretical thermal loading models (TLM-I and TLM-II), and the standardized gradient in Chinese Code JTG D60-2015. The analysis encompasses temperature-induced self-restraint stresses, secondary stresses, and axial deformation in variable-section continuous composite girders. Key findings reveal that code-specified thermal stresses exhibit opposing polarity characteristics at specific locations compared to other models. Quantitative decomposition demonstrates that self-restraint stresses primarily derive from equivalent uniform and nonlinear temperature components, while secondary stresses predominantly originate from equivalent linear and uniform temperature contributions. Axial deformations show 89%–94% dependence on equivalent uniform temperature effects. The developed methodology provides theoretical foundations for refined thermal design of composite bridge structures, addressing critical limitations in current code-specified thermal analysis approaches.